(untitled) (World Economics and Finance Bulletin, 2025)
This article examines the evolving landscape of leasing services and the broader service market against the backdrop of economic modernization. It identifies the principal directions in which leasing has developed—namely digitalization, product diversification, sustainability integration, and enhanced customer experience—and how these shifts reflect broader service-sector trends. Drawing on relevant literature, empirical industry data, and expert insights, the paper highlights how advanced technologies, new financing models, and changing regulatory frameworks shape the trajectory of the leasing industry. The analysis reveals that modernization in the economy encourages more flexible, technology-driven, and value-oriented leasing arrangements that align with clients’ strategic needs.